Răspuns:
Explicație pas cu pas:
a ) x о 2x
x × 2x + x + 2x - 2 = 3
2x² + 3x - 2 - 3 = 0
2x² + 3x - 5 = 0
Δ = b² - 4ac
Δ = 3² - 4 × 2 × ( - 5 )
Δ = 9 - 8 × ( - 5 )
Δ = 9 + 40
Δ = 49 ⇒ √Δ = 7 ;
x₁ / x₂ = ( - b ± √Δ ) / 2a
x₁ = ( - 3 + 7 ) / 2 × ( - 5 )
x₁ = 4 / - 10⁽² = 2 / - 5 ;
x₂ = ( - 3 - 7 ) / 2 × ( - 5 )
x₂ = - 10 / - 10
x₂ = 1.
b ) m о n = - 1
mn + m + n - 2 = - 1
mn + m + n - 2 + 1 = 0
mn + m + n - 1 = 0
( m + 1 ) ( n + 1 ) - 1 = 0
( m + 1 ) ( n + 1 ) = 1
1. m + 1 = 1 ⇒ m = 0 ; n + 1 = 1 ⇒ n = 0 ⇒ ( 1 , 1 ) ;
2. m + 1 = - 1 ⇒ m = - 2 ; n + 1 = - 1 ⇒ n = - 2 ⇒ ( - 2 , - 2 ).